Effectiveness Of Early Mobilization In Restoring Physical Function And Preventing Immobilization In Postoperative Coronary Artery Bypass Graft (Cabg) - Wisnu Guntur Prakoso; Tadi Tadi; Navy Sealsi Adinda Prisca Marina; Abu Bakar (Jurnal Ners, 2025)
The Coronary Artery Bypass Graft (CABG) procedure involves surgical trauma that triggers an inflammatory response, pain, and muscle weakness, so the patient tends to restrict movement. Physiologically, immobilization also reduces blood circulation, increases the risk of thrombosis, and worsens lung function due to lack of early mobilization. This study aims to systematically expose the effect of early mobilization on the recovery of physical function and prevention of immobilization in postoperative coronary artery bypass graft (CABG). The method uses search through 4 main databases, namely PubMed, Scopus, Sciencedirect and ProQuest with a span of 5 years from 2020 to 2025. The literature search used keywords, namely "early mobilization exercises", "immobilization prevention", "physical function", "post-operation CABG". The critical appraisal guidelines of the Joanna Briggs Institute are used for article quality assessment reviews. Results of this study is a total of nine articles were extracted related to early mobilization in the restoration of physical function as well as immobilization prevention in postoperative coronary artery bypass graft (CABG). Overall, the article produced several findings related to the existence of physical recovery and immobilization prevention points that support patients with several types of mobilization interventions ranging from basic to the use of tools implemented using various durations, frequencies and intensities. Early mobilization has a positive impact on the physical and psychological aspects and independence of patients. These findings support the need to implement early mobilization protocols as a standard part of CABG postoperative management, based on patient conditions, to optimize clinical outcomes and prevent immobilization-related complications.